Immunology of Reproduction. Second Part - Pacheco, José (1996)
Main aspects of reproductive and inmunological interactions are presented in this review. In the first part, we outlined the current knowledge of the immune system, the humoral and cellular factors, pregnancy modifications of the immune response, and the role of the fetus and the placenta. In this second part, we complete the lattest aspect, reviewing the interaction of the maternal and fetal inmunological systems. We continue revising the knowledge on antisperm and antiovary antibodies, male immunologic infertility, repeated abortion and fetal losses, and explore immunologic aspects of pregnancy induced hypertension, diabetes and pregnancy, Rh factor immunization, fetal hydrops, vascular connective tissue diseases and pregnancy, autoimmune thrombocytopenic purpura, organ transplantation and immunosupressive drugs, and infections during pregnancy, immunity and preterm delivery, as well as a brief on immunology applied contraception.